Proposal for the integration of the main ports of the colombian Caribbean - Ospina Arias, Juan Carlos
The main ports of the Colombian Caribbean are located in the cities of Santa Marta, Barranquilla and Cartagena; they operate under the state concession scheme and each one carries out commercial, administrative and operative efforts independently. The strategic management policies related to the port expansion and logistics optimization plan of Colombia, compiled in the CONPES documents, point to the integration of the port regions in search of competitiveness and productivity. The present article of reflection, collects a series of ideas proposed by the author, based on consultations made in situ, in Colombian ports as well as bibliographic and internet sources, in turn, of their experience in the logistics and port sector. The purpose of the proposal is to unite the three ports in a single business unit by establishing a cargo and passenger communication corridor, strengthening the expansion of the road network and creating a rail interconnection system between the three cities. The above in pursuit of social, commercial and infrastructure development of the Caribbean region and in general of the central region of the country.